2013
DOI: 10.3846/20294913.2013.798598
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Concept of Diversity Management in Organisations in the Czech Republic and the Slovak Republic – A Research Survey

Abstract: The paper deals with the implementation of diversity management in the czech and Slovak organizations. The aim of the research was to find out how the concept of diversity management is accepted and applied in the czech and Slovak companies. The scale questionnaire of the author's own construction was used for data collection. The questionnaire contained apart from the introductory classification items 25 items divided into three thematic areas: the field of inclusion and justice, the field of diversity manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 6 publications
3
9
0
Order By: Relevance
“…The output from the present research study corresponds with a similar study carried out by Egerová et al [6] in which the above authors compared even the opinions of managers from the Czech Republic and the Slovak Republic (for Slovakia see also [12]). …”
Section: Resultssupporting
confidence: 78%
“…The output from the present research study corresponds with a similar study carried out by Egerová et al [6] in which the above authors compared even the opinions of managers from the Czech Republic and the Slovak Republic (for Slovakia see also [12]). …”
Section: Resultssupporting
confidence: 78%
“…Business world has undergone several changes over the last decades, considering the role of multinational companies (MNCs) as well as small -and medium sized enterprises (SMEs). Moreover, MNCs and SMEs should focus not only on profi t (primary bottom line), but on people (second bottom line) and planet (third bottom line) aspects of their business activities as well Bielik, Smutka, Horská (2010) and Egerová, Jiřincová, Lančarič, Savov (2013).…”
mentioning
confidence: 99%
“…But on the other side, it creates social capital, which strengthens interpersonal relationships and cooperation (Hintošová, 2010). On the one hand, some authors confirmed that the CSR concept became very important for the society based on research of Ambramuszkinová -Pavlíková and Basovníková, 2014), on the other hand, (Egerová et al, 2013) and (Nagyová et al, 2016) described that the corporate social responsibility included the economic, legal, ethical, and philanthropic expectations, which had a big influence on the development of companies and their activities. At present, the principles of responsible business are acquired by more and more companies.…”
Section: Literature Reviewmentioning
confidence: 90%